Extrato enriquecido em der f 1 derivado de Dermatophagoides farinae aumenta a reatividade para anticorpos IgG4 específicos - Santos, Paula Fernandes (2016)
House dust mite antigens are the principal cause of respiratory allergic diseases and Dermatophagoides farinae is one of the most clinically relevant in certain regions, particularly in those with high temperature and low relative air humidity. The allergen-specific immunotherapy (SIT) is a treatment strategy for such diseases, modulating the allergic response, with significant increases of specific IgG4 levels. The present study aimed to fractionate the antigenic extracts of D. farinae and evaluate them in immunoassays concerning to the reactivity of IgE- and IgG4-allegen-specific antibodies in the atopic and nonatopic individuals’ serum. Two fractions, one hydrophilic and other hydrophobic, were obtained and used in the IgE- and IgG4-allergen-specific measurement by ELISA. As control, this assay was also performed with a commercial extract of D. farina from Hollister-Stier. A slot blot assay to specific IgG4 and the measurement of the major allergens in the fractions was also made. The hydrophobic extract presented expressive levels of Der f 1 and undetectable values of Der f 2, while the hydrophilic fraction presented both Der f 1 and Der f 2. Both extracts, either separately or in association, improve the reactivity of specific IgG4, in comparison with the commercial extract. Therefore, the fractions could be useful to monitoring the improvement of specific IgG4 levels in the serum samples of patients sensitized under SIT treatment. In addition the hydrophobic fraction, enriched in Der f 1, could be used as an antigenic extract to evaluate the specific sensitivity of patients and also to the allergen-specific immunotherapy to individuals sensitized to Der f 1 but no Der f 2. Thereby, the use of hydrophobic agent during the allergen extraction process, can make possible to determine the antibody reactivity in a serum sample to a specific allergen or to obtain an more appropriated allergen extract (enriched in Der f 1) and consequently, more efficient for specific treatment of allergic patients to Der f 1, but not to Der f 2.